An Embedded Laser Marking Controller Based on ARM and FPGA Processors - Wang Dongyun; Ye Xinpiao (The Scientific World Journal)
Laser marking is an important branch of the laser information processing technology. The existing laser marking machine based on PC and WINDOWS operating system, are large and inconvenient to move. Still, it cannot work outdoors or in other harsh environments. In order to compensate for the above mentioned disadvantages, this paper proposed an embedded laser marking controller based on ARM and FPGA processors. Based on the principle of laser galvanometer scanning marking, the hardware and software were designed for the application. Experiments showed that this new embedded laser marking controller controls the galvanometers synchronously and could achieve precise marking.